MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) DALAM PEMBELAJARAN INKLUSI - Saiful Anwar (Sustainable Jurnal Kajian Mutu Pendidikan, 2018)
Education is the basic rights of men together. In indonesia, education is the right of every residents and the state of having an obligation to render the said right.This is mandated by the UUD 1945 constitution. For children with special needs, the state provide education services in the form of school (SLB) and as the demands of social reality that develops so came educational model of inclusion of, namely educational model for a child with special needs in public schools where the young children of other students. One of the approaches is through context. Kind of classroom linking between the subject matter with reality student life. The contextual leraning was an answer to an kind of classroom kind of classroom that separates between with reality.